Relationship between gait profile score and clinical assessments of gait in post-stroke patients - Matteo Bigoni; Veronica Cimolin; Luca Vismara; Andrea G. Tarantino; Daniela Clerici; Silvia Baudo; Manuela Galli; Alessandro Mauro (Medical Journals Sweden, 2021)
Background: Gait Profile Score (GPS) was validated as quality measure for the Gait Analysis (GA) in several patholgies, but GPS was never compared with clinical scales in post-stroke patients. Objective: The aim of the study was to quantify functional limitation of post-stroke hemiparetic patients using clinical-functional scales and GPS and to assess the presence of correlation between GPS and the clinical-based outcome scales. Methods: Thirty-three patients were assessed with the Berg Balance Scale (BBS), Trunk Impairment Scale (TIS), Functional Ambulation Category (FAC), Functional Independence Measure (FIM) and Ten-Meter Walk Test (10-MWT); GPS was obtained by GA. Results: GPS showed a fair relationship with FAC (p = 0.017; r = -0.412), TIS (p = 0.011, r = -0.436) and 10-MWT (p = 0.009, r =  0.49) and good correlation with BBS (p = 0.001; r = -0.561). The three regression models were statistically significant: Model 1 showed that FAC, GPS and FIM had a statistically significant effect in the determination of the BBS, in model 2 and 3, FIM presented a statistically significant effect on TIS determination. Conclusion: GPS seems to be an independent linear predictor of balance performance in stroke patient, and GVSs on sagittal plane might help clinicians to investigate the acquired compensatory strategies.